2015
DOI: 10.1007/s00441-015-2316-3
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Chromogranin A deficiency on catecholamine storage, catecholamine granule morphology and chromaffin cell energy metabolism in vivo

Abstract: Chromogranin A (CgA) is a prohormone and granulogenic factor in neuroendocrine tissues with a regulated secretory pathway. The impact of CgA depletion on secretory granule formation has been previously demonstrated in cell culture. However, studies linking the structural effects of CgA deficiency with secretory performance and cell metabolism in the adrenomedullary chromaffin cells in vivo have not previously been reported. Adrenomedullary content of the secreted adrenal catecholamines norepinephrine (NE) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 82 publications
(129 reference statements)
5
65
0
Order By: Relevance
“…Accordingly, transmission electron microscopy (TEM) analysis was performed, following similar procedures to those previously described (Pasqua et al, 2015), to evaluate the mitochondria of both CCN6-siRNAtransfected cells and the corresponding controls. TEM revealed an increased number of mitochondria together with elevated mitochondrial and cristae volume density {cristae volume density (%) = [sum of cristae area (µm 2 ) / mitochondrial area (µm 2 )] × 100}, as well as crista area, in CCN6-depleted cells ( Fig.…”
Section: Ccn6-depleted Cells Have Altered Mitochondrial Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, transmission electron microscopy (TEM) analysis was performed, following similar procedures to those previously described (Pasqua et al, 2015), to evaluate the mitochondria of both CCN6-siRNAtransfected cells and the corresponding controls. TEM revealed an increased number of mitochondria together with elevated mitochondrial and cristae volume density {cristae volume density (%) = [sum of cristae area (µm 2 ) / mitochondrial area (µm 2 )] × 100}, as well as crista area, in CCN6-depleted cells ( Fig.…”
Section: Ccn6-depleted Cells Have Altered Mitochondrial Morphologymentioning
confidence: 99%
“…Samples were anonymized, and morphometric measurements were made randomly from different cells as described previously (Pasqua et al, 2015). The line segment tool in NIH ImageJ 1.49 software was used to measure the distance between ER and mitochondria.…”
Section: Morphometric Analysis Of Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite compensatory effects of other granins in granule biogenesis, CgA knockout mice systematically exhibited an elevation of catecholamine levels, suggesting nevertheless a specific role of CgA in the regulation of catecholamine storage and secretion. More recently, a morphological study of chromaffin cell SG from CgA‐KO mice revealed a decrease in both the diameter and the volume density, and an increase in the ratio between their size and that of their dense core, implying SG swelling that could be due to increased free catecholamines . Altogether, these observations suggest therefore the existence of a link between CgA expression and the formation of functional SG in neuroendocrine cells.…”
Section: Chromogranin a Contributes To The Biogenesis Of Secretory Grmentioning
confidence: 92%
“…CgA has an intracellular function in secretory granule biogenesis [12, 13], as well as important extracellular functions as a precursor of various bioactive peptides involved in the regulation of metabolism, innate immunity, cardiovascular system, vascular contractility, and endothelial barrier function [1, 2]. A growing body of evidence suggests that CgA and its N-terminal fragment 1-76, called vasostatin-1 (VS-1), can also have a role in tumor biology.…”
Section: Introductionmentioning
confidence: 99%